2007
DOI: 10.1515/bot.2007.014
|View full text |Cite
|
Sign up to set email alerts
|

New records of benthic marine algae from the Canary Islands (eastern Atlantic Ocean): morphology, taxonomy and distribution

Abstract: Four species of marine algae are reported from the Canary Islands for the first time. Our report of the western Atlantic Gelidiella setacea (Gelidiales, Rhodophyta) is the first from the eastern Atlantic Ocean. Pseudotetraspora marina (Tetrasporales, Chlorophyta) previously known on the eastern side of the Atlantic Ocean from temperate saltmarshes only, is now reported growing in the shallow sublittoral zone, the habitat in which tropical western Atlantic populations also occur. The presence of Lomentaria chyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…The biogeographical position of the Canary Islands has been recognized as the major element for the richness of its marine biota (Haroun & Herrera, 2001), with a high interest in phycology, where several publications were produced over the years (e.g. Afonso‐Carrillo et al, 2007; Gil‐Rodríguez & Afonso‐Carrillo, 1980; Haroun & Herrera, 2001; Sangil et al, 2012). Therefore, it is no surprise that macroalgae are amongst the most detected NNS taxa in this archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…The biogeographical position of the Canary Islands has been recognized as the major element for the richness of its marine biota (Haroun & Herrera, 2001), with a high interest in phycology, where several publications were produced over the years (e.g. Afonso‐Carrillo et al, 2007; Gil‐Rodríguez & Afonso‐Carrillo, 1980; Haroun & Herrera, 2001; Sangil et al, 2012). Therefore, it is no surprise that macroalgae are amongst the most detected NNS taxa in this archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…Exsiccate vouchers of the new records were deposited in the Herbarium of the Botanical Museum of Curitiba. Morphological taxonomic identification was performed, using as comparative material specialized and illustrated descriptions of the species from the Brazilian oceanic islands (Villaça et al 2006, Burgos 2011, Burgos et al 2009, Pereira-Filho et al 2011, 2015; southeastern (Cordeiro-Marino 1978, Crispino 2007, Coto 2007 (Barnes et al 2015); and the Canary Islands (Sanson et al 2002, Haroun et al 2002, Afonso-Carrillo et al 2007).…”
Section: Sampling Methods and Analysis Of Biological Datamentioning
confidence: 99%
“…This opportunistic group deserves attention as a bioindicator of changes. Similarly, Afonso-Carrillo et al (2007) reported that a subtidal algae bed in the Canary Islands has undergone changes, indicated by the proliferation of the ephemeral green algae Pseudotetraspora marina, a recent and probably introduced species reported for the eastern Atlantic Ocean. Sangil et al (2012) associated the shifts in the distribution and biomass of ephemeral species with the 2°C warming in the SST resulting from the weakening of the cold Canary current.…”
Section: Higher Richness Vs Abiotic Changes: Bridging or Introductions?mentioning
confidence: 91%
See 1 more Smart Citation
“…Esta espécie possui até 3,0 cm de altura e o diâmetro do ramo ereto pode alcançar 150-200 µm (Taylor, 1960), podendo apresentar ramificações. A medula do ramo ereto é constituída de cinco camadas, sendo uma fileira central contendo a célula axial e 2-4 células periaxiais e mais duas camadas de células medulares opostas (Afonso-Carrillo et al, 2007). Mesmo sem a presença de estruturas férteis no espécime deste estudo, as estruturas vegetativas indicam não se tratar de Pa. setaceous, já que o espécime é menor, em altura e diâmetro, não possui ramificações e a medula do ramo ereto é constituída apenas pela fileira central composta pela célula axial e células periaxiais.…”
Section: Observações E Comentáriosunclassified